2009
DOI: 10.1007/s00330-009-1535-y
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography for preoperative assessment of hepatic vasculature and prediction of splenic artery steal syndrome in patients with liver cirrhosis before transplantation

Abstract: The purpose of this study was to evaluate the accuracy of MDCT for preoperative assessment of hepatic vascular anatomy and the identification of liver-transplantation (OLT) patients at risk of developing subsequent splenic artery steal syndrome (SASS). A total of 145 patients with liver cirrhosis who had undergone OLT and had pre-operative three-phase MDCT (4- to 64-rows) within 100 days before OLT were enrolled retrospectively. MDCT and 3Ds were reviewed by two independent blinded observers (O1/O2). Pre-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
0
47
1
2
Order By: Relevance
“…The study of Grieser et al noted that CT-determined splenic volumes greater than 829 mL had a 75% accuracy for prediction of SAS [23]. Other studies describe CT measured splenic artery diameters of over 4 mm and differences of 6 mm between splenic and hepatic artery diameters as pre-operative predictors of patients with SAS [13,14,35].…”
Section: Prediction and Prevention Of Sasmentioning
confidence: 94%
See 1 more Smart Citation
“…The study of Grieser et al noted that CT-determined splenic volumes greater than 829 mL had a 75% accuracy for prediction of SAS [23]. Other studies describe CT measured splenic artery diameters of over 4 mm and differences of 6 mm between splenic and hepatic artery diameters as pre-operative predictors of patients with SAS [13,14,35].…”
Section: Prediction and Prevention Of Sasmentioning
confidence: 94%
“…Reports of leukopenia and thrombocytopenia in SAS patients are other signs of symptomatic hypersplenism [20,21]. If transplant biopsy is performed, histological analysis often reveals mild inflammation in SAS as opposed to the overt findings in acute rejection [22,23].…”
Section: Clinical Presentationmentioning
confidence: 98%
“…In a recent study evaluating the involvement of the SMA, the CHA, and the celiac trunk with multidetector CT using the traditional criteria of circumferential tumor contact and vessel constriction in 70 pancreatic cancer patients, the sensitivity and specificity were increased from 88 % and 94 % for axial images to 100 % and 93 % for additional multiplanar reconstructions [20]. Other recent studies showed similar results with high accuracy for the assessment of arterial invasion for CT and even for MRI using latest generation devices [10,25,26]. These improvements help to increase the rate of correct indications for and successful completions of open surgery with curative intent in pancreatic cancer patients [27].…”
Section: Arteriesmentioning
confidence: 72%
“…This recently could be confirmed with a retrospective radiological evaluation by Grieser et al. [24]. As contraindication for prophylactic treatment, we defined patients with portal vein thrombosis, transjugular intrahepatic portosystemic shunt (TIPSS) or other porto‐caval shunts as they seem to be at a higher risk of developing portal venous thrombosis after OLT [25–29].…”
Section: Discussionmentioning
confidence: 99%